The Influence of Workload and Digital Adaptation on the Performance of Pasaman Police Department Personnel with Job Satisfaction as an Intervening Variable - Antoni Hasibuan; Almasdi Almasdi (Brilliant International Journal Of Management And Tourism, 2026)
The development of information technology and the operational demands of the police force require organizational adjustments to maintain effective task implementation. This study aims to examine the effect of workload and digital adaptation on the performance of Pasaman Police personnel and examine the role of job satisfaction as an intervening variable in this relationship. The study used a quantitative approach with a purposive sample of 180 respondents from a population of 263 personnel. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) after undergoing instrument validity and reliability tests. The analysis results show that digital adaptation has a positive and significant effect on job satisfaction (β = 0.828; p < 0.001), while job satisfaction has a significant positive effect on personnel performance (β = 0.480; p = 0.003). The direct effect of workload on job satisfaction and performance is not significant (p > 0.05). The direct effect of digital adaptation on performance shows a positive direction but is statistically marginal (p ≈ 0.059). Mediation analysis indicated that job satisfaction significantly mediated the relationship between digital adaptation and performance (indirect effect ≈ 0.398; p = 0.003), but did not mediate the relationship between workload and performance. The research model explained approximately 82% of the variance in job satisfaction and approximately 76.7% of the variance in performance (R² ≈ 0.82 and R² ≈ 0.767). The study's conclusions emphasize the importance of strengthening digital adaptation programs and interventions that increase job satisfaction as strategies to improve personnel performance. Practical implications include designing digital training relevant to operational tasks, improving managerial support, and evaluating and structuring workloads based on actual tasks to support the effectiveness of police institutions.